The catalytic domains of thiamine triphosphatase and CyaB-like adenylyl cyclase define a novel superfamily of domains that bind organic phosphates - Iyer, Lakshminarayan M (BioMed Central, 2002)
BACKGROUND: The CyaB protein from Aeromonas hydrophila has been shown to possess adenylyl cyclase activity. While orthologs of this enzyme have been found in some bacteria and archaea, it shows no detectable relationship to the classical nucleotide cyclases. Furthermore, the actual biological functions of these proteins are not clearly understood because they are also present in organisms in which there is no evidence for cyclic nucleotide signaling. RESULTS: We show that the CyaB like adenylyl cyclase and the mammalian thiamine triphosphatases define a novel superfamily of catalytic domains called the CYTH domain that is present in all three superkingdoms of life. Using multiple alignments and secondary structure predictions, we define the catalytic core of these enzymes to contain a novel α+β scaffold with 6 conserved acidic residues and 4 basic residues. Using contextual information obtained from the analysis of gene neighborhoods and domain fusions, we predict that members of this superfamily may play a central role in the interface between nucleotide and polyphosphate metabolism. Additionally, based on contextual information, we identify a novel domain (called CHAD) that is predicted to functionally interact with the CYTH domain-containing enzymes in bacteria and archaea. The CHAD is predicted to be an alpha helical domain, and contains conserved histidines that may be critical for its function. CONCLUSIONS: The phyletic distribution of the CYTH domain suggests that it is an ancient enzymatic domain that was present in the Last Universal Common Ancestor and was involved in nucleotide or organic phosphate metabolism. Based on the conservation of catalytic residues, we predict that CYTH domains are likely to chelate two divalent cations, and exhibit a reaction mechanism that is dependent on two metal ions, analogous to nucleotide cyclases, polymerases and certain phosphoesterases. Our analysis also suggests that the experimentally characterized members of this superfamily, namely adenylyl cyclase and thiamine triphosphatase, are secondary derivatives of proteins that performed an ancient role in polyphosphate and nucleotide metabolism.